2022
DOI: 10.3390/nu14193995
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting—A Healthy Dietary Pattern for Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN), a metabolic disease, is characterized by severe systemic metabolic disorders. A unique dietary pattern, such as intermittent fasting (IF) has shown promising protective effects on various metabolic diseases, such as diabetes and cardiovascular and nervous system diseases. However, its role in regulating kidney disease, especially in DN, is still being investigated. Here, we summarize the current research progress, highlighting the relationship between IF and the risk factors for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…This study also found that urinary L-FABP level in patients with normal albuminuria is higher than that in patients with microalbuminuria regardless of the type of diabetes [40]. Yang [41] et al found that L-FABP expression was significantly increased after intermittent fasting in diabetic nephropathy patients diagnosed by kidney biopsy. In a cross-section study of 106 patients with type 2 diabetes and 30 patients without diabetes, latex-enhanced immunoturbidimetry was used to measure L-FABP and found a significant negative correlation between urinary L-FABP levels and eGFR (r=-0.606, p<0.001).…”
Section: Liver-type Fatty Acid-binding Protein(l-fabp)supporting
confidence: 59%
“…This study also found that urinary L-FABP level in patients with normal albuminuria is higher than that in patients with microalbuminuria regardless of the type of diabetes [40]. Yang [41] et al found that L-FABP expression was significantly increased after intermittent fasting in diabetic nephropathy patients diagnosed by kidney biopsy. In a cross-section study of 106 patients with type 2 diabetes and 30 patients without diabetes, latex-enhanced immunoturbidimetry was used to measure L-FABP and found a significant negative correlation between urinary L-FABP levels and eGFR (r=-0.606, p<0.001).…”
Section: Liver-type Fatty Acid-binding Protein(l-fabp)supporting
confidence: 59%
“…This shift to utilizing fat for energy can lead to more sustained and steady energy levels throughout the day, as opposed to the energy spikes and crashes often associated with frequent meals and carbohydrate-heavy diets. Individuals who practice intermittent fasting often report feeling more alert, focused, and energetic during fasting periods (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial lifestyle changes have been advocated to treat CKD, diet remains relatively underused in the clinics [132,136] . Mechanistically, dietary manipulations might improve renal health via improved function and composition of gut microbiota and therefore changes in the spectrum of microbiota-derived metabolites that may be either nephroprotective (e.g., short-chain fatty acids) or detrimental to renal health (e.g., gut-derived uremic toxins) [136] . Intermittent fasting, a promising approach to delay the progression of CKD, remains under active investigation, particularly in the DN arena [137] .…”
Section: Dieting and Direct Manipulation Of Gut Microbiotamentioning
confidence: 99%